Spontaneous Intracerebral Hemorrhage Due to Delta Storage Pool Disease in a Patient on a Serotonin-Norepinephrine Reuptake Inhibitor - Leibetseder, Annette; Wagner, Judith; Tomasits, Josef; Haring, Hans-Peter; Hutterer, Markus; Trenkler, Johannes; von Oertzen, Tim J. (Frontiers in Neurology, 2019)
We report a case of spontaneous intracerebral hemorrhage due to delta storage pool disease in a 60-year-old female on a serotonin-norepinephrine reuptake inhibitor (SNRI). Increased susceptibility to SNRI-effects on hemostasis was due to a genetic disposition mediated by a polymorphism of the SLC6A4 gene coding for the human serotonin transporter. Pathophysiological and clinical implications of these findings are discussed.